PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PUBLIKASI SUSTAINABILITY REPORT (Studi Empiris pada Perusahaan LQ45 yang Terdaftar di BEI Tahun 2011-2014) - Wulanda, Rhisa Dwi Putri; Hasan, Amir; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Publication of Sustainability Report (SR) in Indonesia is still voluntary, but the interests and priorities of the companies to publish SR increases. This research aims to determine the effect of the characteristics of the company and corporate governance consists of activity analysis, size, audit committee, and board of directors on the publication of sustainability report in LQ45 companies listed in Indonesian Stock Exchange (IDX) in 2011-2014. The data used in this research were secondary data from companies’ financial data listed in Indonesian Stock Exchange. The sampling methods used was non-probability sampling, which is purposive sampling method. From the population of 78 companies listed in the index of LQ45 during 2011-2014, they were counted 12 companies that fill up the criterias. The hypothesis tested by using logistic regression analysis. The results of the hypothesis test showed that activity analysis, size, and board of directors are having significant effects on the publication of sustainability report with 0.01, 0.03 and 0.04 significance. While the audit committee has no significant effect with 0.236 significance. The influence of the characteristics of the company and corporate governance is 65.5% while the remaining 34.5% is influenced by other variables.Keywords : sustainability report, inventory turnover, size, audit committe, board of directors.